A review of NiO-based electrochromic-energy storage bifunctional material and integrated device. (March 2022) - Wang, Junkai; Huo, Xiangtao; Guo, Min; Zhang, Mei
Highlights: The construction of NiO-based electrochromic-energy storage devices was analyzed. The improvement methods of NiO-based pseudocapacitors were summarized. The efforts of NiO-based electrochromic materials were presented. The research progress of NiO-based bifunctional materials or devices was reviewed. The main challenges of NiO bifunctional materials were summarized. Abstract: With the rapid development of economy, energy crisis and environmental pollution have become the focus of whole society. Developing new kinds of materials with dual or multi functions may be the key to resolving the conflict. As a representative capacitor material and also an anodic electrochromic material, NiO has been proved to be a promising bifunctional material for integrated devices such as electrochromic capacitors and/or energy storage smart windows. However, there are still great challenges in engineering between energy storage and electrochromic devices. In this review, the integration feasibility and configuration design of NiO electrochromic-energy storage device are firstly analyzed. The research progress of NiO based pseudocapacitors, electrochromic devices, and electrochromic-energy storage devices are reviewed in detail, and the main challenges and improvement methods are presented. Finally, the efforts toward addressing the critical topics are highlighted, with expectation of achieving bifunctional materials and practical integrated devices in the future.